Development of Stilling Basin Models with Appurtenances - H. L. Tiwari; M S Hora; Bikram Prasad (International Journal of Engineering and Management Research, 2022)
This research paper describes about the experimental work leading to the sustainable hydraulic structures by developing new stilling basin model as compared to USBR VI stilling basin model for pipe outlet using with sills. The experimental study was carried out for three Froude numbers namely 3.85, 2.85 and 1.85 for non-circular pipe outlet. Performance index (PI) has been used to evaluate the performance of stilling basin models tested using same sand base material and test run time. The scour pattern was measured for each test run and flow pattern was also observed. After 21 tests runs, it was found that the performance of stilling basin model improved even by reducing the length of basin from 8.4 d to 6 d by introducing intermediate sill of square cross section along with USBR VI impact wall and end sill. Performance of this model was found to be better than USBR VI impact basin for similar flow condition at reduced length of 6 d from 8.4d where d is the equivalent diameter of pipe outlet.